China's New-Type Urbanisation Plan (NUP) and the foreseeing challenges for decarbonization of cities: a review - Cheshmehzangi, Ali (Elsevier, 2016)
The most recent urbanisation plan in China, the New-type Urbanisation Plan (NUP) launched in March 2014, is a national plan proposed for development of a scientific and reasonable urban development model by 2020. NUP aims to connect four major plans of ecological progress, urbanisation quality, expanding domestic demand and rural-urban coordination. After almost two years, several contradictions are already in place. However, there are key challenges for decarbonization of cities in this process. This review paper explores four major challenges and suggests steps forward during and after NUP's lifespan. This study also elaborates on the processes and contradictions for decarbonization of Chinese cities.